Nanoparticle / modified foamed nickel / epoxy resin high wear-resistant material and preparation method thereof

CN117736546BActive Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311758007.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2026-10-30
Estimated Expiration
2043-12-20

AI Technical Summary

Benefits of technology

[0039](1)本发明提供一种纳米粒子/改性泡沫镍/环氧树脂高耐磨材料,以改性泡沫镍为增强骨架,以掺杂纳米粒子的环氧树脂为基体材料。即以改性泡沫镍作为增强骨架,以环氧树脂作为基体材料,以纳米粒子作为基体材料环氧树脂的增强材料。改性泡沫镍在所述纳米粒子/改性泡沫镍/环氧树脂高耐磨材料中主要起到三维骨架的支撑和散热作用,同时具有收集磨屑以及磨屑润滑的作用;在受到磨损时,纳米粒子可以形成润滑膜,同时在温度较高或者摩擦热积累过高时,纳米粒子能够有效地降低复合材料的热膨胀系数,并在复合材料中形成一定的散热通道,提高导热能力,即纳米粒子在所述纳米粒子/改性泡沫镍/环氧树脂高耐磨材料中主要起到促进环氧树脂基体材料润滑和散热能力的作用;改性泡沫镍和掺杂在环氧树脂中的纳米粒子不仅具有协同增强的润滑性能,还能协同形成连贯的导热网络,在大幅度提高纳米粒子/改性泡沫镍/环氧树脂高耐磨材料的耐磨性能的同时,有效提高其散热性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117736546B_ABST
    Figure CN117736546B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano particle / modification foamed nickel / epoxy resin high wear-resistant material and preparation method thereof, belong to high wear-resistant sliding contact material technical field.The nano particle / modification foamed nickel / epoxy resin high wear-resistant material, with modification foamed nickel as reinforcing framework, with doped nano particle epoxy resin as matrix material.Modification foamed nickel in the nano particle / modification foamed nickel / epoxy resin high wear-resistant material mainly plays the support and heat dissipation effect of three-dimensional framework, simultaneously has the effect of collecting abrasive and abrasive lubrication;Nano particle in the nano particle / modification foamed nickel / epoxy resin high wear-resistant material mainly plays the effect of promoting the lubrication and heat dissipation capacity of epoxy resin matrix material;Modification foamed nickel and doped nano particle in epoxy resin synergistic reinforcement, so that the nano particle / modification foamed nickel / epoxy resin high wear-resistant material has excellent wear resistance and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high wear-resistant sliding contact materials, and in particular to a high wear-resistant material of nanoparticles / modified nickel foam / epoxy resin and its preparation method. Background Technology

[0002] Polymers possess advantages such as good mechanical properties, chemical / corrosion resistance, low density, simple manufacturing, and low cost, and are often used in high-wear-resistant materials for railway transportation systems and motors. Among polymers, epoxy resin, due to its excellent flowability and moldability, is a widely used casting sealant and adhesive material, and has broad prospects in the field of high-wear-resistant materials. To ensure the normal operation of sliding high-wear-resistant materials under long-term high-temperature wear environments, these materials need to possess both high wear resistance and good heat dissipation performance to ensure continuous normal operation. However, epoxy resin has a low thermal conductivity, and in long-term friction environments, the frictional heat accumulated at the interface often cannot dissipate in time, leading to material performance deterioration, severe wear, and even material failure. Therefore, improving the wear resistance and heat dissipation of epoxy resin has always been a significant challenge. To address this issue, some studies have used different discrete particle reinforcing materials, such as short fibers, metal powders, and flake graphite, to improve the wear resistance and heat dissipation capacity of epoxy resin materials. However, these discrete particles are prone to agglomeration and cannot form a continuous heat dissipation path.

[0003] With the increasing complexity and practicality of sliding contact materials, there is an urgent need to research and develop new high-wear-resistant materials that simultaneously possess high thermal conductivity and wear resistance. Summary of the Invention

[0004] The purpose of this invention is to provide a high-wear-resistant material made of nanoparticles / modified nickel foam / epoxy resin and its preparation method, thereby solving the aforementioned problems in the prior art. The high-wear-resistant material made of nanoparticles / modified nickel foam / epoxy resin of this invention possesses both high thermal conductivity and high wear resistance.

[0005] One of the technical solutions of the present invention is a nanoparticle / modified nickel foam / epoxy resin high wear-resistant material, which uses modified nickel foam as a reinforcing skeleton and epoxy resin doped with nanoparticles as a matrix material.

[0006] This material uses modified nickel foam as a reinforcing skeleton, epoxy resin as a matrix material, and nanoparticles as a reinforcing material for the epoxy resin matrix. The modified nickel foam primarily serves as the support and heat dissipation element of the three-dimensional skeleton in this nanoparticle / modified nickel foam / epoxy resin high-wear-resistant material, while also collecting and lubricating wear debris. The nanoparticles mainly enhance the lubrication and heat dissipation capabilities of the epoxy resin matrix material. The synergistic reinforcement of the modified nickel foam and the nanoparticles doped in the epoxy resin gives this high-wear-resistant material excellent wear resistance and thermal conductivity.

[0007] Furthermore, by mass ratio, the modified nickel foam: epoxy resin: nanoparticles = 1.2-1.4:1:0.005-0.015.

[0008] More preferably, the modified nickel foam: epoxy resin: nanoparticles ratio is 1.25:1:0.01 by mass.

[0009] Furthermore, the modified nickel foam is prepared by using hydroxyethyl ethylenediamine to perform surface film-forming modification treatment on nickel foam to obtain the modified nickel foam.

[0010] Furthermore, the surface film-forming modification treatment of nickel foam using hydroxyethyl ethylenediamine includes: heating and immersing the nickel foam in a hydroxyethyl ethylenediamine solution.

[0011] Hydroxyethyl ethylenediamine (HEED) has excellent metal ion chelating ability and can form a protective film on the surface of nickel foam, preventing the nickel foam from reacting with oxygen or water in the environment, thereby slowing down the corrosion rate of the nickel foam. In addition, HEED can also be used as a curing agent for epoxy resin, and can react with epoxy resin to form a cross-linked polymer with excellent properties. Overall, it plays a role in protecting the nickel foam and improving the interfacial bonding ability between epoxy resin and nickel foam.

[0012] Furthermore, the heating and soaking temperature is 50-70℃, and the time is 2-4 hours.

[0013] Furthermore, the described nickel foam is prepared via an industrial-grade electrolytic reduction method. Nickel foam prepared via this method exhibits excellent oxidation resistance, good electrical conductivity and mechanical properties, and is also inexpensive. Moreover, the actual shape and size of the nickel foam can be controlled according to actual needs to meet the requirements of various application environments.

[0014] Furthermore, the nickel foam can be of any porosity, density, and size. In this embodiment, a porosity of 110 PPI and a wire diameter density of 0.5 g / cm³ were specifically used. 3Nickel foam with a wire diameter of 450μm.

[0015] Furthermore, the nanoparticles are one or more of carbon nanophases and nanometal particles (the nanoparticles can be one or more carbon nanophases, one or more nanometal particles, or one or more carbon nanophases + one or more nanometal particles).

[0016] Furthermore, the carbon nanophase includes one or more of functionalized carbon nanotubes, functionalized graphene, and functionalized fullerene; the nano-metal particles include one or more of nano-copper, nano-silver, and nano-nickel.

[0017] The nanoparticles are one or more of functionalized carbon nanotubes, functionalized graphene, functionalized fullerene, copper nanoparticles, silver nanoparticles, and nickel nanoparticles. When the nanoparticles are two or more of functionalized carbon nanotubes, functionalized graphene, functionalized fullerene, copper nanoparticles, silver nanoparticles, and nickel nanoparticles, these two or more nanoparticles can be mixed in any mass ratio, wherein preferably, each type of nanoparticle has the same mass.

[0018] Furthermore, the method for preparing the functionalized carbon nanotubes is as follows: the carbon nanotubes are subjected to carboxylation modification or amination modification to obtain the functionalized carbon nanotubes; the method for preparing the functionalized graphene is as follows: the graphene is subjected to carboxylation modification or amination modification to obtain the functionalized graphene; the method for preparing the functionalized fullerene is as follows: the fullerene is subjected to carboxylation modification or amination modification to obtain the functionalized fullerene.

[0019] Carboxylation or amination of carbon nanophases (carbon nanotubes, graphene, or fullerene) can improve the doping amount and dispersibility of carbon nanophases in epoxy resins, as well as their interfacial bonding ability.

[0020] Furthermore, the carboxylation modification method is as follows: the carbon nanophase is heated and refluxed in a mixed acid solution, and after the heating and reflux are completed, it is filtered, washed, dried, and milled.

[0021] Further, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a 1:1 mass ratio. The filtration and washing are repeated multiple times until the filtrate is neutral. The heating and reflux treatment is performed at a temperature of 110-130℃ for 2-4 hours.

[0022] Furthermore, the method for amination modification is as follows: the carbon nanophase is heated and refluxed in ammonia water, and after the heating and reflux are completed, it is filtered, washed, dried, and milled.

[0023] Further, the concentration of the ammonia solution is 25–28 wt.%. The filtration and washing processes are repeated multiple times until the filtrate is neutral. The heating and reflux treatment is performed at a temperature of 110–130°C for 2–4 hours.

[0024] Furthermore, the carbon nanotubes have an inner diameter of 5–20 nm, an outer diameter of 30–50 nm, and an average length of 10 μm.

[0025] Furthermore, the graphene is preferably sheet-like graphene, wherein the thickness of the sheet-like graphene is 0.55–3.74 nm, the length is 0.5–3 μm, and the width is 0.5–3 μm.

[0026] Furthermore, the epoxy resin is preferably epoxy resin E-51.

[0027] Furthermore, the curing agent is a polyamide curing agent, and the toughening agent is dibutyl phthalate.

[0028] Furthermore, the nanoparticles are preferably functionalized carbon nanotubes obtained by carboxylation modification and functionalized graphene (sheet graphene) obtained by amination modification, wherein the mass ratio of the functionalized carbon nanotubes to the functionalized graphene is 1:1.

[0029] Multi-walled carbon nanotubes (MWC nanotubes) are modified by carboxylation, introducing carboxyl groups onto their surface. Graphene is modified by amination, introducing amination groups onto its surface. These modifications result in finer MWC nanotubes and graphene. The presence of these surface groups facilitates the adhesion of organic or inorganic materials, promoting better dispersion and arrangement of nanoparticles within the matrix, improving interfacial properties, and enhancing interfacial interactions. This improves the solubility of carbon nanotubes and graphene, allowing them to be uniformly and effectively dispersed within the epoxy resin. Furthermore, MWC nanotubes and graphene possess excellent lubrication and thermal conductivity. As reinforcing materials for epoxy resin, they can synergistically form a lubricating film and shorten film formation time during wear. Simultaneously, at high temperatures or with excessive frictional heat accumulation, the functionalized MWC nanotubes and graphene effectively reduce the thermal expansion coefficient of the composite material and form heat dissipation channels within it, improving thermal conductivity.

[0030] The second technical solution of the present invention: A method for preparing the above-mentioned nanoparticle / modified nickel foam / epoxy resin high wear-resistant material, comprising the following steps: preheating epoxy resin and nanoparticles; heating the preheated epoxy resin; sequentially adding the preheated nanoparticles, curing agent and toughening agent to the heated epoxy resin, stirring, and ultrasonically treating to obtain a mixture; pouring the mixture into modified nickel foam in a mold, ultrasonically treating, and heating to cure (the mixture naturally flows and seeps in during the pouring, ultrasonic treatment and heating to cure) to obtain the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material.

[0031] Furthermore, the preheating treatment temperature is 50-70℃, and the time is 0.5-2h (preheating is to reduce the viscosity of epoxy resin, ensuring that the epoxy resin is easier to mix and flow); the heating treatment temperature is 190-210℃, and the time is 2-4min (heating is to make the epoxy resin form a liquid state, which is conducive to casting); the ultrasonic treatment time is 3-5min (ultrasonic treatment is to reduce air bubbles in the mixture); by mass ratio, epoxy resin: curing agent: toughening agent = 1:0.30~0.40:0.09~0.11.

[0032] Furthermore, the ultrasonic power of the ultrasonic treatment is 40 kHz.

[0033] Furthermore, the heating and curing temperature is 40-60℃, and the time is 4-6 hours.

[0034] Furthermore, the heating and curing is carried out in a water bath. The purpose of the water bath is to extend the curing time of the sample and allow the epoxy resin mixture to be fully filled.

[0035] Furthermore, before pouring the mixture into the modified nickel foam in the mold, the process further includes the step of laying the modified nickel foam at the bottom of the mold cavity.

[0036] The third technical solution of the present invention: the application of the above-mentioned nanoparticle / modified nickel foam / epoxy resin high wear-resistant material in railway transportation systems or motors.

[0037] Furthermore, the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material is used as a high wear-resistant contact material for railway transportation systems or motors.

[0038] The present invention discloses the following technical effects:

[0039] (1) This invention provides a high wear-resistant material of nanoparticles / modified nickel foam / epoxy resin, with modified nickel foam as the reinforcing skeleton and epoxy resin doped with nanoparticles as the matrix material. That is, a material with modified nickel foam as the reinforcing skeleton, epoxy resin as the matrix material, and nanoparticles as the reinforcing material of epoxy resin. In the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material, modified nickel foam mainly serves as a three-dimensional framework for support and heat dissipation, while also collecting and lubricating wear debris. When subjected to wear, the nanoparticles can form a lubricating film. Furthermore, at higher temperatures or when frictional heat accumulation is excessive, the nanoparticles effectively reduce the coefficient of thermal expansion of the composite material and form heat dissipation channels within it, improving thermal conductivity. In other words, the nanoparticles primarily promote the lubrication and heat dissipation capabilities of the epoxy resin matrix in this nanoparticle / modified nickel foam / epoxy resin high wear-resistant material. The modified nickel foam and the nanoparticles doped in the epoxy resin not only synergistically enhance lubrication performance but also synergistically form a continuous thermally conductive network, significantly improving both the wear resistance and heat dissipation performance of the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material.

[0040] (2) The nanoparticle / modified nickel foam / epoxy resin high wear-resistant material of the present invention has both high thermal conductivity and wear resistance. Its wear amount is reduced by 57% compared with pure epoxy resin wear-resistant material, and its thermal conductivity reaches 5.722 (W / m·k). Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0042] Figure 1 The images are scanning electron microscope (SEM) images of the microstructure of nickel foam, where (a) is a low-magnification image and (b) is a high-magnification image.

[0043] Figure 2 The images are scanning electron microscope (SEM) images of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material finally prepared in Example 1, where (a) is a low magnification image and (b) is a high magnification image.

[0044] Figure 3 The image shows the distribution of functionalized carbon nanotubes and functionalized graphene nanoparticles in the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material finally prepared in Example 1.

[0045] Figure 4The wear morphology of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material prepared in Example 1 after wear is shown in the scanning electron microscope image. Figure 4 As shown, (a) is the low magnification chart and (b) is the high magnification chart;

[0046] Figure 5 Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), EP prepared in Comparative Example 1, 1.0 wt.% nanoparticles / EP prepared in Comparative Example 2, Ni prepared in Comparative Example 3 f / EP, Ni prepared in Comparative Example 4 f / (1.0 wt.% functionalized carbon nanotubes / EP), Ni prepared in Comparative Example 5 f Comparison of friction coefficients over time for (1.0 wt.% functionalized graphene / EP);

[0047] Figure 6 Ni prepared for Comparative Example 3 f / EP, Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), Ni prepared in Example 2 f / (0.5wt.%functionalized nanoparticles / EP), Ni prepared in Example 3 f Comparison of friction coefficient changes over time for (1.5 wt.% functionalized nanoparticles / EP);

[0048] Figure 7 Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), EP prepared in Comparative Example 1, 1.0 wt.% nanoparticles / EP prepared in Comparative Example 2, Ni prepared in Comparative Example 3 f / EP, Ni prepared in Comparative Example 4 f / (1.0 wt.% functionalized carbon nanotubes / EP), Ni prepared in Comparative Example 5 f Comparison of cross-sectional changes in the wear trajectory of (1.0 wt.% functionalized graphene / EP);

[0049] Figure 8 Ni prepared for Comparative Example 3 f / EP, Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), Ni prepared in Example 2 f / (0.5wt.%functionalized nanoparticles / EP), Ni prepared in Example 3 f Comparison of cross-sectional changes in the wear trajectory of / (1.5wt.%functionalized nanoparticles / EP);

[0050] Figure 9 Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), EP prepared in Comparative Example 1, 1.0 wt.% nanoparticles / EP prepared in Comparative Example 2, Ni prepared in Comparative Example 3 f / EP, Ni prepared in Comparative Example 4 f / (1.0 wt.% functionalized carbon nanotubes / EP), Ni prepared in Comparative Example 5 f Thermal conductivity comparison chart of (1.0 wt.% functionalized graphene / EP);

[0051] Figure 10 Ni prepared for Comparative Example 3 f / EP, Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), Ni prepared in Example 2 f / (0.5wt.%functionalized nanoparticles / EP), Ni prepared in Example 3 f Thermal conductivity comparison chart of (1.5wt.%) functionalized nanoparticles / EP. Detailed Implementation

[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0053] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0054] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0055] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0056] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0057] The nickel foam used in the following examples and comparative examples is nickel foam prepared by industrial-grade electrolytic reduction, with a pore size of 110 PPI and a wire diameter density of 0.5 g / cm³. 3 The wire diameter is 450μm and it was purchased from Kunshan Xingzhenghong Electronic Materials Co., Ltd.

[0058] The multi-walled carbon nanotubes (MWCNTs) used in the following examples and comparative examples have an inner diameter of 5–20 nm, an outer diameter of 30–50 nm, and an average length of 10 μm.

[0059] The sheet graphene (G) used in the following examples and comparative examples has a thickness of 0.55–3.74 nm, a length of 0.5–3 μm, and a width of 0.5–3 μm.

[0060] The nano-nickel used in the following examples and comparative examples is powder with an average particle size of 25 nm.

[0061] The epoxy resin used in the following examples and comparative examples is epoxy resin E-51, the curing agent is polyamide 651, and the toughening agent is dibutyl phthalate.

[0062] The concentrated sulfuric acid used in the following examples and comparative examples had a concentration of 98 wt%, and the concentrated nitric acid had a concentration of 68 wt%.

[0063] Example 1

[0064] (1) Modification treatment of nickel foam (surface film formation treatment): Nickel foam is immersed in hydroxyethyl ethylenediamine solution at 60℃ for 3h to form a protective film on the surface of nickel foam, thus obtaining modified nickel foam.

[0065] (2) Modification of multi-walled carbon nanotubes (carboxylation modification): Prepare a 300ml mixed acid solution by mixing concentrated sulfuric acid and concentrated nitric acid in a 1:1 mass ratio. Place a certain amount of multi-walled carbon nanotubes in a beaker, add the above mixed acid solution to submerge them, and slowly stir with a glass rod until homogeneous. Then transfer the solution to a three-necked flask and heat under constant temperature electric heating mantle at 120℃ for 3 hours to fully oxidize the multi-walled carbon nanotubes. Then perform multiple filtrations and wash with deionized water until the multi-walled carbon nanotubes are neutral. Transfer the washed multi-walled carbon nanotubes to a clean beaker, and then use a freeze dryer to dry the multi-walled carbon nanotubes. Finally, grind them to a particle size of about 2000 mesh (after grinding, pass through a 2000 mesh sieve) to obtain functionalized multi-walled carbon nanotube nanoparticles.

[0066] (3) Modification treatment of sheet graphene (amylation treatment): A certain amount of sheet graphene was added to a beaker containing 300 ml of ammonia water (concentration of 28 wt%), and stirred slowly with a glass rod until uniform. The mixture was then transferred to a three-necked flask and heated under constant temperature electric heating mantle at 120°C for 3 hours to fully treat the sheet graphene. Then, the mixture was filtered multiple times and washed with deionized water until the sheet graphene was neutral. The washed sheet graphene was transferred to a clean beaker and dried using a freeze dryer. Then, it was milled to a particle size of about 2000 mesh (after milling, it was passed through a 2000 mesh sieve) to obtain functionalized sheet graphene nanoparticles.

[0067] (4) Casting preparation of nanoparticle / modified nickel foam / epoxy resin high wear-resistant material: Epoxy resin, functionalized multi-walled carbon nanotube nanoparticles and functionalized sheet graphene nanoparticles were placed in a constant temperature drying oven at 60℃ for preheating to reduce the viscosity of epoxy resin and ensure that the epoxy resin is easier to mix and flow. After preheating for 1 hour, A (preheated epoxy resin), B (preheated functionalized multi-walled carbon nanotube nanoparticles) and C (preheated functionalized sheet graphene nanoparticles) were obtained. A was heated on a heating stage at 200℃ for 3 minutes, and B and C (0.5% of the epoxy resin mass respectively), curing agent (35% of the epoxy resin mass), and toughening agent (10% of the epoxy resin mass) were added in sequence and stirred for 3 minutes. Then, ultrasonic treatment was performed for 3 minutes (power of 40KHz to reduce bubbles) to obtain mixture D (epoxy resin doped with functionalized nanoparticles). Mixture D was used as a filler and poured into modified nickel foam in a silicone rubber mold (the mass ratio of epoxy resin to modified nickel foam in mixture D was 1:1.25, i.e., the mass ratio of modified nickel foam, epoxy resin, functionalized multi-walled carbon nanotube nanoparticles, and functionalized sheet graphene nanoparticles was 1.25:1:0.005:0.005; modified nickel foam was pre-laid at the bottom of the cavity of the silicone rubber mold). After ultrasonic treatment for 3 minutes (power at 40 kHz), the sample was placed in a 50°C water bath for static heating and curing for 5 hours. After cooling, it was demolded to obtain a high wear-resistant material of functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin (referred to as Ni). f / (1.0wt.%functionalized nanoparticles / EP)).

[0068] Example 2

[0069] Same as Example 1, except that in step (4), the mass ratio of modified nickel foam, epoxy resin, functionalized multi-walled carbon nanotube nanoparticles, and functionalized sheet graphene nanoparticles is 1.25:1:0.0025:0.0025. The resulting high wear-resistant material is simply referred to as Ni. f / (0.5wt.%functionalized nanoparticles / EP).

[0070] Example 3

[0071] Same as Example 1, except that in step (4), the mass ratio of modified nickel foam, epoxy resin, functionalized multi-walled carbon nanotube nanoparticles, and functionalized sheet graphene nanoparticles is 1.25:1:0.0075:0.0075. The resulting high wear-resistant material is simply referred to as Ni. f / (1.5wt.%functionalized nanoparticles / EP).

[0072] Example 4

[0073] (1) Modification treatment of nickel foam (surface film formation treatment): Nickel foam is immersed in hydroxyethyl ethylenediamine solution at 60℃ for 3h to form a protective film on the surface of nickel foam, thus obtaining modified nickel foam.

[0074] (2) Casting preparation of nanoparticle / modified nickel foam / epoxy resin high wear-resistant material: Epoxy resin and nano-nickel were placed in a constant temperature drying oven at 60℃ for preheating to reduce the viscosity of epoxy resin and ensure that epoxy resin is easier to mix and flow. After preheating for 1 hour, A (preheated epoxy resin) and E (preheated metallic nickel) were obtained. A was heated on a heating table at 200℃ for 3 minutes. E (0.5% of the mass of epoxy resin), curing agent (35% of the mass of epoxy resin), and toughening agent (10% of the mass of epoxy resin) were added in sequence and stirred for 3 minutes. Then, the mixture was ultrasonically treated for 3 minutes (power of 40KHz to reduce bubbles) to obtain mixture D (epoxy resin doped with nanoparticles). Mixture D was used as a filler and poured into modified nickel foam in a silicone rubber mold (the mass ratio of epoxy resin to modified nickel foam in mixture D was 1:1.25, i.e., the mass ratio of modified nickel foam, epoxy resin, and nano-nickel was 1.25:1:0.01; the modified nickel foam was pre-laid at the bottom of the cavity of the silicone rubber mold). After ultrasonic treatment for 3 minutes (power at 40 kHz), the sample was placed in a 50°C water bath for static heating and curing for 5 hours. After cooling, it was demolded to obtain a functionalized nano-nickel / (modified) nickel foam / epoxy resin high wear-resistant material (referred to as Ni). f / (1.0wt.% nanoparticles / EP)).

[0075] Comparative Example 1

[0076] Preparation of high-wear-resistant epoxy resin material by casting: Epoxy resin was preheated in a constant temperature drying oven at 60℃ for 1 hour to obtain A. A was heated on a heating platform at 200℃ for 3 minutes, and curing agent (35% of the epoxy resin mass) and toughening agent (10% of the epoxy resin mass) were added sequentially, and stirred for 3 minutes. Then, it was ultrasonically treated for 3 minutes (power at 40KHz to reduce air bubbles) to obtain mixture D. Mixture D was used as a filler and cast into a silicone rubber mold. After ultrasonic treatment for 3 minutes (power at 40KHz), the sample was placed in a water bath at 50℃ for static heating and curing for 5 hours. After cooling, it was demolded to obtain high-wear-resistant epoxy resin material (EP).

[0077] The difference between this comparative example and Example 1 is that there is no modified nickel foam skeleton and no functionalized nanoparticles are added to the epoxy resin.

[0078] Comparative Example 2

[0079] Same as Example 1, except that step (1) is omitted and no modified nickel foam is used in the silicone rubber mold in step (4). The ultrasonically treated mixture D is directly poured into the silicone rubber mold as a filler. After ultrasonic treatment for 3 minutes (power of 40KHz), the sample is placed in a water bath at 50℃ and heated and cured for 5 hours. After cooling, the sample is demolded to obtain functionalized carbon nanotube-functionalized graphene / epoxy resin high wear-resistant material (abbreviated as 1.0wt.% nanoparticles / EP).

[0080] Comparative Example 3

[0081] (1) Modification treatment of nickel foam (surface film formation treatment): The nickel foam is immersed in a hydroxyethyl ethylenediamine solution at 60°C for 3 hours to form a protective film on the surface of the nickel foam.

[0082] (2) Preparation of modified nickel foam / epoxy resin high wear-resistant material by casting: Preheat epoxy resin in a constant temperature drying oven at 60℃ for 1 hour to obtain A. Heat A on a heating platform at 200℃ for 3 minutes, add curing agent (35% of the mass of epoxy resin) and toughening agent (10% of the mass of epoxy resin) in sequence, stir for 3 minutes, and then sonicate for 3 minutes (to reduce bubbles) to obtain mixture D. Cast mixture D as filler into modified nickel foam in a silicone rubber mold (the mass ratio of mixture D to modified nickel foam is 1:1.25, and the modified nickel foam is pre-laid at the bottom of the cavity of the silicone rubber mold), sonicate for 3 minutes (power is 40KHz), place the sample in a water bath at 50℃ and let it stand for heating and curing for 5 hours, and demold after cooling to obtain modified nickel foam / epoxy resin high wear-resistant material (referred to as Ni). f / EP).

[0083] The difference between this comparative example and Example 1 is that no functionalized nanoparticles were added to the epoxy resin.

[0084] Comparative Example 4

[0085] Similar to Example 1, except that step (3) is omitted. The mixed solution in step (4) consists of functionalized multi-walled carbon nanotube nanoparticles (added at 1.0% of the epoxy resin mass), epoxy resin, curing agent, and toughening agent. The addition of functionalized sheet graphene nanoparticles is omitted. The mass ratio of modified nickel foam, epoxy resin, and functionalized multi-walled carbon nanotube nanoparticles is 1.25:1:0.01. Finally, a functionalized carbon nanotube / modified nickel foam / epoxy resin high wear-resistant material (referred to as Ni) is obtained. f / (1.0wt.%functionalized carbon nanotubes / EP)).

[0086] Comparative Example 5

[0087] Similar to Example 1, except that step (2) is omitted. The mixed solution in step (4) consists of functionalized sheet graphene nanoparticles (added at 1.0% of the epoxy resin mass), epoxy resin, curing agent, and toughening agent. The addition of functionalized multi-walled carbon nanotubes is omitted. The mass ratio of modified nickel foam, epoxy resin, and functionalized sheet graphene nanoparticles is 1.25:1:0.01. Finally, a functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material (referred to as Ni) is obtained. f / (1.0wt.% functionalized graphene / EP)).

[0088] Comparative Example 6

[0089] Same as Example 1, except that step (1) is omitted, and unmodified nickel foam is used instead of the modified nickel foam in the silicone rubber mold in step (4). The final product is a functionalized carbon nanotube-functionalized graphene / nickel foam / epoxy resin high wear-resistant material.

[0090] Comparative Example 7

[0091] Same as Example 1, except that step (2) is omitted and unfunctionalized multi-walled carbon nanotubes are used instead of functionalized multi-walled carbon nanotubes in step (4). The final product is a carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high-wear-resistant material.

[0092] Comparative Example 8

[0093] Same as Example 1, except that step (3) is omitted and unfunctionalized sheet graphene is used instead of functionalized sheet graphene in step (4). The final product is a functionalized carbon nanotube-graphene / modified nickel foam / epoxy resin high wear-resistant material.

[0094] Effect verification

[0095] 1. Morphological structure

[0096] Scanning electron microscope image of the microstructure of raw material nickel foam is shown below. Figure 1 As shown, (a) is a low-magnification image and (b) is a high-magnification image. The raw material used, nickel foam, has a smooth surface, a dense skeleton, and a connected three-dimensional structure. This allows nickel foam to not only give the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material excellent wear resistance, but also to form a complete heat dissipation path. Furthermore, the presence of nickel foam gives the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material high strength and impact resistance. These advantages can meet the requirements of various new wear-resistant materials.

[0097] The scanning electron microscope (SEM) image of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material finally prepared in Example 1 is shown below. Figure 2As shown in the diagram, (a) is a low-magnification image and (b) is a high-magnification image. It can be clearly seen that the epoxy resin doped with functionalized multi-walled carbon nanotubes and functionalized sheet graphene nanoparticles is relatively uniform and dense, and the overall surface is very smooth, which is beneficial for leveraging the reinforcing and lubricating potential of the functionalized carbon nanotubes and functionalized graphene nanoparticles. It can also be seen that the modified nickel foam is effectively filled by the epoxy resin doped with functionalized multi-walled carbon nanotubes and functionalized sheet graphene nanoparticles. The interface between the epoxy resin doped with functionalized multi-walled carbon nanotubes and functionalized sheet graphene nanoparticles and the modified nickel foam is also relatively uniform and tight, which is beneficial for the modified nickel foam to play a supporting and conductive role in the epoxy resin matrix material. With the introduction of modified nickel foam, a distinct 3D nickel metal framework network structure is formed within the composite material.

[0098] The scanning electron microscope (SEM) image of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high wear-resistant material finally prepared in Example 1 is shown below. Figure 3 As shown, functionalized carbon nanotubes and functionalized graphene are effectively distributed in the matrix epoxy resin of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin composite material.

[0099] The tribological properties of the samples were tested using a multifunctional tribological testing instrument (MS-M9000). The friction was conducted using a pin-disc friction method with surface-to-surface contact, with steel balls as the friction pair material. The test mode was rotation. Before the experiment, the sample surface was polished to a roughness Ra = 0.2 μm. The experiment was conducted at room temperature with a load of 15 N and a rotation speed of 120 r / min, with a single friction cycle of 1 h. The sample used for the tribological test was a cylinder with dimensions of Φ30 × 2 mm. The SEM image of the wear morphology of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin high-wear-resistant material finally prepared in Example 1 after wear is shown below. Figure 4 As shown, (a) is a low-magnification image and (b) is a high-magnification image. The lubricating effect of functionalized multi-walled carbon nanotube nanoparticles and functionalized sheet graphene nanoparticles doped in epoxy resin is beneficial to the rapid formation of a lubricating film during wear. Moreover, the nickel skeleton has good strength and a smooth lubricating surface, which is conducive to the collection of wear debris, shortens the film formation cycle, and effectively reduces the wear of the composite material.

[0100] 2. Wear resistance and heat dissipation

[0101] The friction coefficient, wear rate, and thermal conductivity of high wear-resistant materials were tested using the following methods:

[0102] (1) The tribological properties of epoxy resin-based composite materials were tested using a multifunctional tribological testing instrument (MS-M9000, Lanzhou, China). The friction was conducted using a pin-disc friction method with surface-to-surface contact. The friction pair material was a copper-chromium alloy ball, and the test mode was rotation. Before the experiment, the sample surface was polished to a roughness Ra = 0.2 μm. The experiment was conducted at room temperature with a load of 15 N and a rotation speed of 120 r / min, with a single friction cycle of 1 h. The sample used for the tribological test was a cylinder with dimensions of Φ30 × 2 mm.

[0103] (2) The thermal conductivity of epoxy resin-based composite materials was tested using a thermal conductivity meter (Hot Disk TPS2500S, Hot Disk AB, Sweden). Due to equipment requirements, all samples tested were cylindrical specimens with dimensions of Φ30×2mm.

[0104] Figure 5 , Figure 7 , Figure 9 Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), EP prepared in Comparative Example 1, 1.0 wt.% nanoparticles / EP prepared in Comparative Example 2, Ni prepared in Comparative Example 3 f / EP, Ni prepared in Comparative Example 4 f / (1.0 wt.% functionalized carbon nanotubes / EP), Ni prepared in Comparative Example 5 f The graphs show a comparison of the coefficient of friction over time for (1.0 wt.% functionalized graphene / EP), a comparison of the cross-sectional changes of the wear trajectory (the horizontal axis represents the distance the test rod moves perpendicular to the wear trajectory, and the vertical axis represents the change in the cross-sectional area of ​​the wear trajectory), and a comparison of thermal conductivity. Figure 6 , Figure 8 and Figure 10 Ni prepared in Comparative Example 3 f / EP, Ni prepared in Example 1 f / (1.0 wt.% functionalized nanoparticles / EP), Ni prepared in Example 2 f / (0.5wt.%functionalized nanoparticles / EP), Ni prepared in Example 3 f Comparison of friction coefficient over time, cross-sectional changes of wear trajectory, and thermal conductivity of (1.5 wt.% functionalized nanoparticles / EP).

[0105] The wear resistance and heat dissipation test results of each embodiment and comparative example are summarized in Table 1. The friction coefficient in Table 1 is the average friction coefficient after it tends to level off, that is, the average friction coefficient in the 45-60 min segment of the friction coefficient change curve over time.

[0106] Table 1

[0107]

[0108] As can be seen from the data comparison of Example 1 and Comparative Examples 1-5, when functionalized multi-walled carbon nanotube nanoparticles and functionalized sheet graphene nanoparticles are introduced into epoxy resin as reinforcing materials and modified nickel foam is used as the skeleton, the high wear-resistant material (Example 1) shows the best wear resistance and heat dissipation. The wear amount of the composite material is reduced by 57% compared with the pure EP wear-resistant material, and the thermal conductivity reaches 4.722 (W / m·k). Modified nickel foam primarily serves as a three-dimensional framework and dissipates heat in nanoparticle / modified copper foam / epoxy resin high wear-resistant materials, while also collecting and lubricating wear debris. Nanoparticles doped in epoxy resin mainly enhance the lubrication and heat dissipation capabilities of the epoxy resin matrix. The synergistic effect of modified nickel foam and epoxy resin-doped nanoparticles enhances the wear resistance and thermal conductivity of the nanoparticle / modified nickel foam / epoxy resin high wear-resistant materials, enabling them to achieve optimal wear resistance and heat dissipation.

[0109] When the total mass fraction of functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles introduced into epoxy resin is 0.5% of the epoxy resin (0.25% each of functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles), the coefficient of friction of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin composite material is 0.455, and the wear is 0.07128 mm. 2 The thermal conductivity is 4.976 (W / m·K). When the total mass fraction of functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles introduced into the epoxy resin is 1.5% (functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles each account for 0.75%), the coefficient of friction of the functionalized carbon nanotube-functionalized graphene / foam-modified nickel foam / epoxy resin composite material is 0.431, and the wear is 0.0627 mm. 2 The thermal conductivity is 4.591 (W / m·K). When the total mass fraction of functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles introduced into the epoxy resin is 1% (functionalized multi-walled carbon nanotube nanoparticles and functionalized graphene nanoparticles each account for 0.5%), the coefficient of friction of the functionalized carbon nanotube-functionalized graphene / modified nickel foam / epoxy resin composite material is 0.435, and the wear is 0.05781 mm. 2 With a thermal conductivity of 4.722 (W / m·k), it exhibits the best wear resistance and optimal heat dissipation performance.

[0110] The data above shows that the composite material obtained by modifying nickel foam, multi-walled carbon nanotubes and graphene has the best wear resistance and heat dissipation performance.

[0111] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A nanoparticle / modified nickel foam / epoxy resin high wear-resistant material, characterized in that, Modified nickel foam is used as the reinforcing skeleton, and epoxy resin doped with nanoparticles is used as the matrix material. By mass ratio, modified nickel foam: epoxy resin: nanoparticles = 1.2-1.4:1:0.005-0.015; The preparation steps of the modified nickel foam are as follows: surface film-forming modification treatment is performed on nickel foam using hydroxyethyl ethylenediamine to obtain the modified nickel foam; The nanoparticles are one or more of carbon nanophase and nano-metal particles; The carbon nanophase includes functionalized carbon nanotubes and functionalized graphene; the nano-metal particles include nano-nickel. The preparation steps of the functionalized carbon nanotubes are as follows: the carbon nanotubes are modified by carboxylation to obtain the functionalized carbon nanotubes; the preparation steps of the functionalized graphene are as follows: the graphene is modified by amination to obtain the functionalized graphene.

2. The nanoparticle / modified nickel foam / epoxy resin high wear-resistant material as described in claim 1, characterized in that, The surface film modification treatment of nickel foam using hydroxyethyl ethylenediamine includes: heating and immersing the nickel foam in a hydroxyethyl ethylenediamine solution.

3. A method for preparing a high-wear-resistant nanoparticle / modified nickel foam / epoxy resin material as described in any one of claims 1-2, characterized in that, The process includes the following steps: preheating epoxy resin and nanoparticles; heating the preheated epoxy resin; sequentially adding the preheated nanoparticles, curing agent, and toughening agent to the heated epoxy resin; stirring and ultrasonically treating to obtain a mixture; pouring the mixture into modified nickel foam in a mold; ultrasonically treating; heating and curing; and demolding to obtain the nanoparticle / modified nickel foam / epoxy resin high wear-resistant material.

4. The preparation method according to claim 3, characterized in that, The preheating treatment is performed at a temperature of 50-70℃ for 0.5-2 hours; the heating treatment is performed at a temperature of 190-210℃ for 2-4 minutes; the ultrasonic treatment is performed for 3-5 minutes; and the epoxy resin: curing agent: toughening agent ratio is 1:0.30-0.40:0.09-0.11 by mass.

5. The application of a high wear-resistant nanoparticle / modified nickel foam / epoxy resin material as described in any one of claims 1-2 in a railway transportation system or an electric motor.

Citation Information

Patent Citations

  • Foam framework enhanced polymer composite material and preparation method thereof

    CN105733192A

  • Thermal conductive electromagnetic shielding composite material and preparation method and application thereof

    CN109943023A